Participatory design of a virtual reality life review therapy system for palliative care - Ng, Royce; Woo, Olive Kit Ling; Eckhoff, Daniel; Zhu, Mengyao; Lee, Antoinette; Cassinelli, Alvaro (Frontiers in Virtual Reality, 2024)
We present a novel Virtual Reality (VR) life review therapy system. Life review therapy is an intervention used by clinical psychologists, counselors, and social workers for patients under palliative care to systematically examine various life experiences to resolve conflicts and complete life tasks. The goal of the therapy is to narrativize the patient's life before death in order to come to terms with their mortality. Our VR life review therapy system allows therapists to perform their interventions in customized virtual spaces designed to encourage the patient to reflect and reminisce about their life experiences. Our system is also developed in response to mobility restrictions and COVID-19 pandemic-related quarantine measures that have separated patients under palliative care from family and friends, resulting in emotional and psychological distress. As VR systems related to health are increasingly being used by therapists in their interventions, it is of utmost importance that the health professionals who will be the end users of these systems are involved in the design process to create ethical healthcare technologies. In response, we initiated the participatory design and evaluation of our VR life review therapy system prototype with six clinical psychologists who have practical experience delivering life review therapy to patients in palliative care in the Hong Kong hospital system. In the study, each participant experienced the VR life review therapy system and evaluated its strengths and weaknesses through semistructured interviews. The qualitative data gathered from these interviews was coded according to nine different categories; avatars, content design, evaluation, haptic sensations, interaction, gesturing and gaze direction, movement and navigation, non-verbal communication, soundtrack. These conceptual categories were chosen based on our analysis of common themes reported by the clinical psychologists' experience of the system. Feedback from clinical psychologists on each of these categories was incorporated into the redesign and update of the final system.Overall, participants generally evaluated the system as feasible and effective for use with patients under palliative care, while movement and interaction were the features requiring the most improvement.